Atomically dispersed main group magnesium on cadmium sulfide as the active site for promoting photocatalytic hydrogen evolution catalysis - Chen, Ran (2022)
Photoabsorption charge separation/transfer and surface reaction are the three main factors influencing the efficiency of photocatalysis. Band structure engineering has been extensively applied to improve the light absorption of photocatalysts, however, most of the developed photocatalysts still suffer from low photocatalytic performance due to the limited active site(s) and fast recombination of photogenerated charge carriers. In this work, atomically dispersed main group magnesium (Mg) is introduced onto CdS monodispersed nanospheres, which greatly enhances the photocatalytic hydrogen evolution reaction. The photocatalytic hydrogen evolution reaction rate reaches 30.6 mmol·gcatalyst-1·h-1, which is about 11.8 and 2.5 times that of pure CdS and Pt (2 wt.%)-CdS. The atomically dispersed Mg on CdS acts as an electron sink to trap photogenerated electrons, and at the same time, greatly reduces the Gibbs free energy of hydrogen evolution reaction (HER) and accelerates HER.